Pharmacognostic Studies on Two Himalayan Species of Traditional Medicinal Value: Allium wallichii and Allium stracheyi - Umeshkumar TIWARI; Sebastian J. ADAMS; Noorunnisa BEGUM S; Kulithalai V. KRISHNAMURTHY; Kaliamoorthy RAVIKUMAR; Venkatasubramanian PADMA (Notulae Scientia Biologicae, 2014)
The present research was aimed as a pharmacognostic study of whole plants of Allium wallichii and Allium stracheyi, both of which are very important traditional medicinal plants of North-West Himalayas. This study was carried out in terms of macroscopic and microscopic analyses and standard histochemical methods were followed for detecting starch, calcium oxalate, tannins, total lipids and alkaloids. Allium wallichi can be distinguished from A. stracheyi by possessing polyarch roots, mycorrhizal fungi in the outer cortical cells and triangular leaf midrib. The present study is the first to describe the pharmacognosy in terms of anatomical and histochemical features of these two Himalayan Allium species. Although they are listed in Ayurvedic database, the API so far has not given an account on these two species and hence this work is of high importance. Also, the herbal industries, researchers and traditional medicine can now use the distinguishing characters of these species listed in the current paper, while specifically acquiring them from local markets without any confusion.